Different faces of the stethoscope: history, usefulness, evolution, contamination, and disinfection practices - Dorota Ochońska; Monika Brzychczy-Włoch; Katarzyna Talaga-Ćwiertnia (Studia Medyczne)
A stethoscope is a tool mainly used by physicians of various specialties in their daily work. Over the centuries, newer designs of this diagnostic tool have been improved and developed. A stethoscope in medical practice, which comes into contact with many patients, poses a high risk of infection transmission and thus may increase the incidence of infection in healthcare facilities. Research data indicate that a stethoscope can be contaminated by 21–100% with clinically relevant bacterial pathogens, including multidrug-resistant strains. A stethoscope is considered non-critical equipment, and the recommendations for cleaning the stethoscope are after each patient, once a day, or once a week. However, there are still no clear-cut algorithms for its handling. The use of disinfectants requires the selection of a suitable agent that, with frequent disinfection of stethoscopes, will not damage sensitive parts and at the same time effectively remove pathogens.